The efficiency of nitrogen utilization of growing lambs fed maize gluten meal as the protein supplement - Piasentier E.; Bovolenta S.; Susmel P.; Diaconescu S. (Recent advances in small ruminant nutrition, 1997)
Three pelleted diets were formulated with a variable quantity of maize meal and maize gluten meal (diet MG0: 69 per cent; diet MG9: 60 per cent and 9 per cent; diet MG18: 51 and 18 per cent, respectively). Each diet was offered to a group of 12 Bergamasca lambs, half males and half females (25 kg initial weight, LW) at a daily rate of 100 g per kg LW0.75. The ME content of the diets was derived from measured faecal and urinary losses and estimated methane losses; the PDI content was derived from the in situ rumen degradability measured on the male lambs by mobile bags recovered at slaughter. Half of the animals were slaughtered at 45 kg LW and the others at 60 kg and their body composition was determined. The initial body fat and protein content was estimated from a control group of comparable 25 kg LW lambs. The inclusion of MG in the diet progressively reduced the ME content (from 11.4 to 10.8 MJ per kg DM) and the effective degradability of the N (from 0.41 to 0.33), but increased the proportion of feed protein absorbed in the intestine. The increase of the MG level determined higher growth rates and a reduction in the fat per Nstar6.25 ratio of the empty-body gain. The PDI efficiency for Nstar6.25 body retention diminished from 0.41 in the MG0 diet to 0.22 in the MG18 diet. For each g per MJ ME of incremental PDI due to the substitution of maize by MG, the Nstar6.25 deposition increased by a value between 0.105 and 0.004 g, according to the stage of physiological maturity of the lambs.
Seminar of the FAO-CIHEAM Network of Cooperative Research on Sheep and Goats, Subnetwork on Nutrition, 24-26 Oct 1996, Rabat (Morocco)